(untitled) (Historia, 2021)
This article will position the African horsesickness (AHS) disease within the context of the broader development of veterinary science in South Africa. It is important to understand the role of the horse, and specifically the effects of AHS, in order to comprehend the rapid development of veterinary science in South Africa during the period stretching from the 1890s to the 1920s.